Insights on the formation of longitudinal surface structures on ice sheets from analysis of their spacing, spatial distribution, and relationship to ice thickness and flow. Issue 4 (20th April 2017) - Ely, J. C.; Clark, C. D.; Ng, F. S. L.; Spagnolo, M.
Abstract: Longitudinal surface structures (LSSs) are prevalent upon the ice streams, ice shelves, and outlet glaciers of ice sheets. These features inform our understanding of past and present ice sheet behavior. However, consensus regarding their genesis has not been reached. Here we analyze 42, 311 LSS segments mapped across Antarctica together with geophysical data to determine their morphological and glaciological properties. Most LSSs are spaced 450 to 1500 m apart, a distance positively correlated with the width of the ice flow unit on which they occur. The start points (upstream end locations) of LSSs have diverse ice thicknesses and velocities. The majority of LSSs occur where ice flow is converging or broadly parallel, and they are prominent at ice confluences. Some occur at slow‐flowing ice stream onsets. Occasionally, LSSs relate to sudden variations in basal shear stress due to basal perturbations. From these observations, we argue that LSSs are the consequence of increased strain which occurs during the lateral compression and longitudinal extension of ice: (i) converging/flowing into a channel (this scenario characterizes most LSSs), (ii) at the onset of ice streaming, (iii) at flow unit confluence, and (iv) as ice flows over and around a basal perturbation. Key Points: Longitudinal surface structures are often used to inform about past configurations of ice sheets, but their formation is debated Analysis of the morphological and glaciological properties of >40, 000 longitudinal surface structures across Antarctica We propose that longitudinal surface structures are the consequence of increased strain encountered by ice in four flow configurations